2006
DOI: 10.1007/s11517-006-0030-8
|View full text |Cite
|
Sign up to set email alerts
|

Heart sound cancellation from lung sound recordings using time-frequency filtering

Abstract: During lung sound recordings, heart sounds (HS) interfere with clinical interpretation of lung sounds over the low frequency components which is significant especially at low flow rates. Hence, it is desirable to cancel the effect of HS on lung sound records. In this paper, a novel HS cancellation method is presented. This method first localizes HS segments using multiresolution decomposition of the wavelet transform coefficients, then removes those segments from the original lung sound record and estimates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 21 publications
0
28
0
1
Order By: Relevance
“…High Pass Filtering (HPF) with an arbitrary cut-off frequency between 70 and 100 Hz is not efficient in this case because lung sounds have major components in that region particularly at low flow rates. Therefore, HS reduction from lung sounds without altering the main characteristic features of the lung sound has been of interest for many researchers [12].…”
Section: Hs Cancellationmentioning
confidence: 99%
“…High Pass Filtering (HPF) with an arbitrary cut-off frequency between 70 and 100 Hz is not efficient in this case because lung sounds have major components in that region particularly at low flow rates. Therefore, HS reduction from lung sounds without altering the main characteristic features of the lung sound has been of interest for many researchers [12].…”
Section: Hs Cancellationmentioning
confidence: 99%
“…before another source can be extracted following the same procedure, equations (6)(7)(8)(9)(10)(11)(12)(13). This extraction is computationally simple when compared with other AJD algorithms [14].…”
Section: Signal Extraction Algorithmmentioning
confidence: 99%
“…Although experimental results were promising, the method suffers from high computational load. Time-frequency (TF) filtering techniques have also been proposed for HSS reduction in LSS [8] and [9], of which the technique employed in [9] is computationally efficient [9] but the results are unconvincing. Recently, for the case of only a single measurement sensor, an adaptive line enhancer was employed to mitigate the HSS in LSS, which yielded promising results [10].…”
Section: Introductionmentioning
confidence: 99%
“…For lung sound analysis, signal processing strategies based on conventional time, frequency, or time-frequency signal representations have been proposed for heart sound cancelation. Representative strategies include entropy calculation (7) and recurrence time statistics (8) for heart sound detection-and-removal followed by lung sound prediction, adaptive filtering (e.g., (9; 10)), time-frequency spectrogram filtering (11), and time-frequency wavelet filtering (e.g., (12)(13)(14)). Subjective assessment, however, has suggested that due to the temporal and spectral overlap between heart and lung sounds, heart sound removal may result in noisy or possibly "non-recognizable" lung sounds (15).…”
Section: Introductionmentioning
confidence: 99%